2015
DOI: 10.1039/c4ra13662d
|View full text |Cite
|
Sign up to set email alerts
|

Application of combined plasma-catalytic method for carbon particulate matter (PM) removal

Abstract: The carbon particulate matter (PM) generated by diesel engine emissions has attracted world-wide attention because it has a remarkable impact on air quality and the human body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Although the PM and NO x purification technology by catalysis‐combined NTP has been developed greatly, the shortcomings of low energy utilization,poor selectivity of target products, catalyst poisoning, and high back pressure caused by catalyst carrier have not yet been overcome 5 . Nano‐CeO 2 , as the redox reaction catalyst, has excellent oxygen storage capacity, delivery capacity, and the resistance of sulfur poisoning capacity 12 . It can improve the target product selectivity in a chemical reaction and definitely plays an important role in the removal of PM and NO x.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the PM and NO x purification technology by catalysis‐combined NTP has been developed greatly, the shortcomings of low energy utilization,poor selectivity of target products, catalyst poisoning, and high back pressure caused by catalyst carrier have not yet been overcome 5 . Nano‐CeO 2 , as the redox reaction catalyst, has excellent oxygen storage capacity, delivery capacity, and the resistance of sulfur poisoning capacity 12 . It can improve the target product selectivity in a chemical reaction and definitely plays an important role in the removal of PM and NO x.…”
Section: Introductionmentioning
confidence: 99%
“…5 Nano-CeO 2 , as the redox reaction catalyst, has excellent oxygen storage capacity, delivery capacity, and the resistance of sulfur poisoning capacity. 12 It can improve the target product selectivity in a chemical reaction and definitely plays an important role in the removal of PM and NO x. 13 Wood fiber is a kind of natural porous biomass material containing a large number of different diameter pores, which can not only adsorb PM, including nanoscale particulates but also serve as catalyst carriers with low back pressure.…”
mentioning
confidence: 99%
“…One technique is to use NTP to generate oxidative radicals for the regeneration of DPFs by low-temperature oxidation of the accumulated DPM in the DPF. The combination of heterogeneous catalysts into the NTP regeneration process can improve the oxidation in terms of energy efficiency and product selectivity. For example, Liu et al reported that the oxidation efficiency of simulated DPM on MnO x (5 wt %)/CeO 2 catalysts is as high as 85.2% under conditions of a 20 °C gas temperature, 18.0 W of discharge power, and 30 mL/min of air flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…One technique is to use NTP to generate oxidative radicals for the regeneration of DPFs by low-temperature oxidation of the accumulated DPM in the DPF. The combination of heterogeneous catalysts into the NTP regeneration process can improve the oxidation in terms of energy efficiency and product selectivity. For example, Liu et al reported that the oxidation efficiency of simulated DPM on MnO x (5 wt %)/CeO 2 catalysts is as high as 85.2% under conditions of a 20 °C gas temperature, 18.0 W of discharge power, and 30 mL/min of air flow rate. Ranji-Burachaloo et al found that in the presence of transition metal oxides, the DPM oxidation efficiency and CO 2 selectivity can be enhanced by 77% and 29%, respectively, as compared to the plasma alone process.…”
Section: Introductionmentioning
confidence: 99%
“…11 Owing to the great concern on the health risks of PM, developing PM control technologies is crucial and urgent. 12 Several techniques including ltering, 13,14 centrifugal cyclone separation, 15 and the use of an electrostatic precipitator (ESP) 16,17 have been widely used for PM removal under ambient conditions. ESP can precipitate PM in the air by using an electrical eld with very little pressure drop.…”
Section: Introductionmentioning
confidence: 99%